(untitled) (Mūzikas akadēmijas raksti, 2024)
Philosophy does not provide for a unitary answer to the question concerning the essence of music and musical work. Owing to the increase in the human understanding of things and the employed philosophical approach, a multitude of interpretations of musical work comes to the foreground. Research into the ontology of musical work or, in other words, into its essence and interpretation proves to be giving an insight into a multitude of problems which are linked with issues of phenomenology and hermeneutics, based on the philosophical views of Edmund Husserl, Martin Heidegger and Hans-Georg Gadamer. Their philosophical standing is further developed by such 20th century music philosophers as Roman Ingarden, Alfred Schütz, Stephen Davies, Ellis Bruce Benson and others. On the one hand, every musical work possesses such omnipresent structures of ontology as a notion of objectiveness and phenomenology, pure intentionality, quasi-temporality, and, on the other hand, – a possibility to interpret a music piece increasingly differently, involving young incoming people. The above factors add an absolutely distinctive meaning to every single performance of music. Musical work already at its very origin incorporates a multitude of interpretations the same as every single piece of notation is potentially characterized by inherent sonority. As to the essence and interpretation, they are correlated, namely, various interpretations.